KOMPENSASI DAN MOTIVASI KERJA PENGARUHNYA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Muhamad Rifa'i; Rosalia Sela; Rr Nugraheni Suci Sayekti (J-MACC, 2021)
This study empirically tested the effect of compensation and work motivation on employee performance directly or indirectly mediated by job satisfaction as intervening variables. This research uses a quantitative approach. Data is primary data collected using questionnaires. The data is analyzed using a path analysis model using the Smart-PLS program. The results of the study showed that partial compensation has a significant and positive influence on job satisfaction Work motivation has a significant positive influence on job satisfaction Compensation has no influence on employee performance. Work motivation has no effect on employee performance. Job satisfaction has a significant and positive influence on employee performance. Compensation has an insorant and positive effect on employee performance through job satisfaction. Work motivation has a significant and positive effect on employee performance that is mediated by job satisfaction.